1982
DOI: 10.1177/036354658201000507
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of men's and women's professional basketball injuries

Abstract: Injuries sustained by male and female professional basketball teams were compared. Injuries from two consecutive seasons were coded, and computer-based cross-tabulations comparing sex, body part, and type of injury were performed. The women's injury frequency was 1.6 times that of men. The body part most frequently injured on both teams was the ankle. Women sustained significantly more knee and thigh injuries as well as sprains, strains, and contusions. Men had significantly more muscle spasms. Other injuries … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
146
1
6

Year Published

1990
1990
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 256 publications
(156 citation statements)
references
References 3 publications
3
146
1
6
Order By: Relevance
“…Table 2 also summarizes disability days for men and women by sport. Women gymnasts had the highest rate of disability, 7.44 days per 100 person-hours of exposure, while men gymnasts had only 1.15 disability days, a sixfold difference (p = .0004). We were unable to detect gender differences in any of the remaining seven sports and, more importantly, when all eight sports were combined.…”
Section: Resultsmentioning
confidence: 91%
“…Table 2 also summarizes disability days for men and women by sport. Women gymnasts had the highest rate of disability, 7.44 days per 100 person-hours of exposure, while men gymnasts had only 1.15 disability days, a sixfold difference (p = .0004). We were unable to detect gender differences in any of the remaining seven sports and, more importantly, when all eight sports were combined.…”
Section: Resultsmentioning
confidence: 91%
“…Recently, injury of the ACL has been reported to be two to eight times higher in women than in men participating in the same sports. Previous studies have indicated noncontact mechanisms as the reason for ACL tears in women, which make these injuries even more perplexing [1,2,4,7,8,12,20].…”
Section: Introductionmentioning
confidence: 99%
“…7,10,23,25,34,47 Consequently, there is currently an increased emphasis in sports medicine on the development of training programs designed to decrease the incidence of noncontact ACL injury in female athletes. 5,6,17,21 In addition to reducing the incidence of ACL injuries, 6,17,21,23 these programs have been shown to also improve lower extremity biomechanics during athletic tasks, while increasing athletic performance.…”
mentioning
confidence: 99%